Cars of the future: the Internet of Things in the automotive industry. (September 2015) - Kirk, Richard
Abstract : The Internet of Things (IoT) regularly hits the headlines and frankly it is exciting to imagine a world where we can control literally everything from a smartphone. Or is it? It is all too easy to get swept along with the relentless advances in connected devices that we are experiencing, but perhaps there is also a contrarian viewpoint that we need to consider. As companies such as Google, Apple and BMW forge ahead with driverless cars and applying the Internet of things (IoT) in transport, it's easy to get carried away by the relentless advances in connected devices. But how will all these innovations be kept secure and how can we be sure users will be safe when our transport could be accessed via the Internet? Richard Kirk of AlienVault, discusses the future risks of IoT in transport, how technological advances have made this possible, and how a lack of a security-oriented mindset is threatening the industry.